Engineering bacteria for high-performance three-dimensional carbon nanofiber aerogel. (15th October 2021) - Wang, Jie; Wan, Yizao; Xun, Xiaowei; Zheng, Liyun; Zhang, Quanchao; Zhang, Zhaohui; Xie, Yu-Xin; Luo, Honglin; Yang, Zhiwei
Abstract: Compared with carbon nanotube (CNT) and graphene (GE) aerogels, the synthesis of three-dimensional (3D) carbon nanofiber (CNF) aerogels that are highly compressible, resilient under cyclic strains, and creep and fatigue resistant remains extremely challenging. Herein, a revolutionary green and scalable biosynthesis is presented, by which a novel 3D CNF aerogel derived from natural bacterial cellulose (BC) decorated with its mother bacteria is created. The as-prepared CNF aerogel possesses excellent mechanical resilience, ultra-low energy loss coefficient, and outstanding cycling stability, which are by far among the best performances for CNT and GE aerogels reported thus far. Furthermore, the CNF aerogel exhibits excellent creep and fatigue resistance and sensitive electrical conductivity change upon compression. Surprisingly, the as-prepared 3D CNF aerogel exhibits superhydrophilicity. These superb properties are attributed to the existing carbonized bacteria in the carbonized BC matrix that serve as crosslinks to strengthen the aerogel and buffers to store deformation energy. This study presents a breakthrough method for the construction of superb and cost-effective 3D CNF aerogel from natural biomass material. Graphical abstract: Image 1 Highlights: A novel 3D carbon nanofiber aerogel is fabricated by carbonizing bacterial cellulose and its mother bacteria. Carbon nanofiber aerogel displays supercompressibility, precise pressure sensing behavior, and excellent creep and fatigue resistance. 3D carbon nanofiber aerogel demonstrates superhydrophilicity.